Consider Water and Sewer Rate Affordability. Issue 3 (5th March 2019) - Qureshi, Naeem; Hanson, Ryan
Abstract : The need to reconstruct crumbling US water infrastructure is staggering. Water/wastewater utilities are struggling to fund cost increases resulting from infrastructure renewal and replacement needs, more stringent regulatory requirements, and other cost pressures. This has resulted in rate increases about three times the rate of inflation.